2022
DOI: 10.1155/2022/4866531
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Adaptive Neural Network Algorithm Model in English Text Analysis

Abstract: Based on the existing optimization neural network algorithm, this paper introduces a simple and computationally efficient adaptive mechanism (adaptive exponential decay rate). By applying the adaptive mechanism to the Adadelta algorithm, it can be seen that AEDR-Adadelta acquires the learning rate dynamically and adaptively. At the same time, by proposing an adaptive exponential decay rate, the number and method of configuring hyperparameters can be reduced, and different learning rates can be effectively obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In recent years, as deep learning has made significant gains in the field of artificial intelligence, researchers have experimented with deep learning to analyse the coherence of text, and some progress has been made. M Hung et al [21] used deep learning methods to construct a model for English text coherence analysis, which performed well in English text coherence diagnosis. Vasamsetti Srinivas et al [22] used deep neural networks to build pre-trained language models to learn text features, and also made research progress.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, as deep learning has made significant gains in the field of artificial intelligence, researchers have experimented with deep learning to analyse the coherence of text, and some progress has been made. M Hung et al [21] used deep learning methods to construct a model for English text coherence analysis, which performed well in English text coherence diagnosis. Vasamsetti Srinivas et al [22] used deep neural networks to build pre-trained language models to learn text features, and also made research progress.…”
Section: Related Workmentioning
confidence: 99%
“…The data set consisted of the ICNALE [29], COLEN [30], CELC [31] and TECCL [32] corpora. One thousand articles were selected from the ICNALE corpus under the same essay topic as the test set for incoherent sentence extraction; 100 unlabelled plain-text English texts from the COLEN corpus were selected as the test set for sentence ranking experiments on this model.…”
Section: Data Set and Model Evaluation Criteriamentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%